2012
DOI: 10.1111/j.1600-0854.2011.01320.x
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus L2 Facilitates Viral Escape from Late Endosomes via Sorting Nexin 17

Abstract: The Human Papillomavirus (HPV) L2 capsid protein plays an essential role during the early stages of viral infection, but the molecular mechanisms underlying its mode of action remain obscure. Using a proteomic approach we have identified the adaptor protein, Sorting Nexin 17 (SNX17) as a strong interacting partner of HPV L2. This interaction occurs through a highly conserved SNX17 consensus binding motif, which is present in the majority of HPV L2 proteins analysed. Using mutants of L2 defective for SNX17 inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
123
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(134 citation statements)
references
References 49 publications
4
123
0
1
Order By: Relevance
“…However, the retromer is in the cytoplasm whereas the incoming virus is initially in the lumen of the endosome. We speculate either that the virus "piggybacks" a ride with a cellular retromer cargo or adapter protein [such as sorting nexin 17 (22,40)], which extends across the endosomal membrane, or that conformational changes in the capsid during disassembly in the endosome lumen expose a hydrophobic segment of L1 or L2, which can embed in the endosomal membrane and protrude into the cytoplasm where it can bind to the retromer. A transmembrane domain exists in the N terminus of L2 (41), and escape of HPV from the endosome and subsequent transport to the nucleus requires a hydrophobic C-terminal segment of the L2 protein, which can disrupt membranes and target proteins to membranes (21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the retromer is in the cytoplasm whereas the incoming virus is initially in the lumen of the endosome. We speculate either that the virus "piggybacks" a ride with a cellular retromer cargo or adapter protein [such as sorting nexin 17 (22,40)], which extends across the endosomal membrane, or that conformational changes in the capsid during disassembly in the endosome lumen expose a hydrophobic segment of L1 or L2, which can embed in the endosomal membrane and protrude into the cytoplasm where it can bind to the retromer. A transmembrane domain exists in the N terminus of L2 (41), and escape of HPV from the endosome and subsequent transport to the nucleus requires a hydrophobic C-terminal segment of the L2 protein, which can disrupt membranes and target proteins to membranes (21).…”
Section: Discussionmentioning
confidence: 99%
“…One study concluded that HPV16 traffics through the endoplasmic reticulum (ER) (11). The L2 protein appears to be important for proper intracellular trafficking, as does binding of sorting nexin 17 to an internal segment of L2 (21)(22)(23).…”
mentioning
confidence: 99%
“…DiGiuseppe and coworkers revealed that L2 amino acid residues 64 to 81 and 163 to 170 and the L2 C-terminal exposure on the cytosolic side of intracellular membranes enable interaction with cytosolic host cell factors (39). Interactions of L2 with actin (40), components of the retrograde transport machinery (37,41,42), sorting nexins 17 and 27, TSG101, ␥-secretase, and Hsc70, as well as the microtubule network, have been reported (37,(41)(42)(43)(44)(45)(46)(47)(48). These interactions result in trafficking to the Golgi network (37,41,42,47), transport toward the nucleus (43,44), and accumulation at nuclear substructures (49)(50)(51)(52)(53).…”
mentioning
confidence: 99%
“…Host cell cyclophilins release the majority of L1 from the L2 protein, which remains in complex with the viral genome (2,23,24). A large portion of the L2 protein translocates across the endocytic membrane to engage factors, including the retromer complex, dynein, sorting nexins, and rab GTPases, that mediate transport to the trans-Golgi network (TGN) (25)(26)(27)(28)(29)(30)(31)(32)(33)). An siRNA screen has suggested that nuclear pore complexes are not required for nuclear entry, but that nuclear envelope breakdown during mitosis is necessary (34,35).…”
mentioning
confidence: 99%